Biphasic osteochondral scaffold fabrication using multi-material mask projection stereolithography. Issue 2 (18th October 2018) - Wu, Xiangquan; Lian, Qin; Li, Dichen; Jin, Zhongmin
Abstract : Purpose: This study aims to develop a multi-material stereolithography (MMSL) technique to directly fabricate a biphasic osteochondral scaffold. Design/methodology/approach: A bespoke prototype MMSL system was developed based on a bottom-up mask projection approach. The system was controlled by a multi-material fabrication algorithm with minimum number of switching cycles during fabrication. A variable-power light source was used to fabricate materials with significantly different curing characteristics. The light-curable poly(ethylene glycol) diacrylate (PEGDA) hydrogel and beta-tricalcium phosphate (β-TCP) ceramic suspension were used for fabricating the biphasic osteochondral scaffold. Findings: The bonding strength of the multi-material interface is shown to be mainly affected by the type of photopolymer, rather than the switching of the materials in MMSL. Lighting power densities of 2.64 and 14.98 mW/cm2 were used for curing the PEGDA hydrogel and the ß-TCP ceramic suspension, respectively. A biphasic osteochondral scaffold with complex interface was successfully fabricated. Originality/value: This study proposes a potential technical method (MMSL) for manufacturing a complex biphasic osteochondral scaffold composing a PEGDA hydrogel/ß-TCP ceramic composite in a time-efficient and precise manner. The designed bone-cartilage scaffold interface and the surface of the cartilage scaffold can be precisely manufactured.